Clinical profile of acute rheumatic fever patients attending a tertiary care hospital in eastern Bihar, India - Suman, Shanker; Kumar, Rakesh; Jyoti, Divya; Agrawal, Pramod Kumar; Parmar, Vishal (International Journal of Advances in Medicine, 2017)
Background: Acute rheumatic fever (ARF) is a multisystem disease resulting from an autoimmune reaction to infection with group A beta haemolytic streptococcus. Acute rheumatic fever commonly occurs between 5-14 years of age.1 The major concern relating to acute rheumatic fever is often not the episode itself but the long-term consequences of damage to heart valves (Rheumatic heart disease (RHD) that often results from recurrent episodes of acute rheumatic fever. Rheumatic heart disease (RHD) continues to be a major public health problem and a common cause of morbidity and mortality in many parts of India.2 Methods: 50 consecutive patients admitted with the diagnosis of acute rheumatic fever in Medicine Department, Katihar Medical College and Hospital, Bihar, India were studied. A detailed clinical history of these patients including presenting symptoms were noted. Physical examination of all systems was done and a diagnosis of acte rheumatic fever was made according to WHO Criteria (2002-2003) for the diagnosis of rheumatic fever and rheumatic heart disease (Based on the Revised Jones Criteria). Echocardiography of all 50 patients were done. Results: Mean age of patients diagnosed with ARF was 14.20±7.02 years. Out of 50 patients, 32 (64%) were female and 18 (36%) were male. Joint pain was the commonest presenting complain, 35 (70%) patients, followed by fever in 21 (42%) patients. Among Jones major manifestations 36 (72%) cases had carditis, 32 (64%) had arthritis, 6 (12%) had subcutaneous nodules, 5 (10%) had erythema marginatum and5(10%) had Sydenham’s chorea. In patients with carditis, 25 (69.44%) had mitral regurgitation (MR) only while 10 (27.77%) had MR with aortic regurgitation (AR) and 1 (2.77%) patient had organic tricuspid regurgitation (TR) with mitral regurgitation and aortic regurgitation. Out of 36 patients with carditis, 10 (27.77%) patients did not have any clinical evidence of carditis and were detected by echocardiography only. Conclusions: Commonest complain in patients with rheumatic fever was joint pain followed by fever. In patients with carditis, all had mitral regurgitation(MR), with 1/3rd of these patients having associated aortic regurgitation(AR). 1/3rd of patients with carditis were detected by echo only and therefore, echo should be included in diagnostic criteria for acute rheumatic fever. None of the patients who developed rheumatic fever was on penicillin prophylaxis.